1998
DOI: 10.1016/s0014-5793(98)00911-9
|View full text |Cite
|
Sign up to set email alerts
|

Operation of glyoxylate cycle in halophilic archaea: presence of malate synthase and isocitrate lyase in Haloferax volcanii

Abstract: The occurrence of the glyoxylate cycle has not previously been demonstrated in any of the Archaea. In halophilic archaea, only isocitrate lyase activity has been detected. The halophilic archaeon Haloferax volcanii was tested for the presence of the other key enzyme of this pathway, malate synthase. High activities of this enzyme were detected when the carbon source was acetate. Both glyoxylate cycle key enzymes, isocitrate lyase and malate synthase, from Hf. volcanii were purified and characterized.z 1998 Fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 34 publications
(58 reference statements)
7
52
0
Order By: Relevance
“…This means that isocitrate lyase and isocitrate dehydrogenase directly compete for isocitrate. The kinetic parameters of isocitrate dehydrogenase are normally better than those of isocitrate lyase: for example, the Haloferax volcanii enzymes have the K m value to isocitrate of 0.13 and 1.16 mM, respectively (Camacho et al, 1995;Serrano et al, 1998). Therefore, the functioning of isocitrate lyase in the presence of isocitrate dehydrogenase requires a large pool of isocitrate, overproduction of isocitrate lyase, or complicated regulation mechanisms controlling isocitrate dehydrogenase activity like, for example, phosphorylation in enterobacteria (El-Mansi et al, 1994;Cozzone and El-Mansi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This means that isocitrate lyase and isocitrate dehydrogenase directly compete for isocitrate. The kinetic parameters of isocitrate dehydrogenase are normally better than those of isocitrate lyase: for example, the Haloferax volcanii enzymes have the K m value to isocitrate of 0.13 and 1.16 mM, respectively (Camacho et al, 1995;Serrano et al, 1998). Therefore, the functioning of isocitrate lyase in the presence of isocitrate dehydrogenase requires a large pool of isocitrate, overproduction of isocitrate lyase, or complicated regulation mechanisms controlling isocitrate dehydrogenase activity like, for example, phosphorylation in enterobacteria (El-Mansi et al, 1994;Cozzone and El-Mansi, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that some halophilic archaea are able to use not only amino acids but different metabolites as well, as, for example, Haloferax mediterranei, which grows in a minimal medium containing glucose as the only source of carbon using a modified Entner-Doudoroff pathway (Rodriguez-Valera et al, 1983), or Haloferax volcanii, which is also able to grow in minimal medium with acetate as the sole carbon source (Kauri et al, 1990). Isocitrate lyase and malate synthase activities were detected in this organism when it was grown on a medium with acetate as the main carbon source (Serrano et al, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Protein concentration was determined as described by Bradford [6,25], using boving serum albumin as standard.…”
Section: B Enzyme Assays and Determination Of Protein Concentrationmentioning
confidence: 99%
“…The gloxylate cycle, which was first proposed by Kornberg and Krebs [1,2] in bacteria growing on acetate [3], is an anaplerotic metabolic pathway which plays an important role in the biogenesis of carbohydrates from C2 compounds [4,5].There are alternative pathways to the glyoxylate cycle in some bacteria [6][7][8].This pathway is widespread in living organisms (Bacteria, Eukarya and Archaea), and the two key enzymes (isocitrate lyase and malate synthase) have been detected in various eubacteria, fungi, plants and even some animals [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation